2015
DOI: 10.1007/s00063-015-0120-1
|View full text |Cite
|
Sign up to set email alerts
|

Medizinrechtliche Aspekte bei der notärztlichen Versorgung

Abstract: AHCDs appear to have an influence in the emergency medical decision process. However, it is presently unclear as to what a standardized and universally comprehensible AHCD should look like, in order to provide a framework that is both acceptable and necessary in a prehospital emergency medicine environment, ensuring medicolegal certainty for the parties involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 26 publications
1
0
0
1
Order By: Relevance
“…In a questionnaire survey of physicians and relatives, Leder et al found that agreement about the practical meaning of advance directives containing widely used, prewritten wording was assessed as low, and that this form of advance directive therefore appeared unsuited to the intensive care setting (21). Similar findings have been reported by other groups (22,23). A retrospective cohort study of 477 patients who had died in intensive care showed that resuscitation was carried out less often in patients who had an advance directive (24).…”
Section: Discussionsupporting
confidence: 85%
“…In a questionnaire survey of physicians and relatives, Leder et al found that agreement about the practical meaning of advance directives containing widely used, prewritten wording was assessed as low, and that this form of advance directive therefore appeared unsuited to the intensive care setting (21). Similar findings have been reported by other groups (22,23). A retrospective cohort study of 477 patients who had died in intensive care showed that resuscitation was carried out less often in patients who had an advance directive (24).…”
Section: Discussionsupporting
confidence: 85%
“…To satisfy the principles of medical ethics under the terms of emergency medicine and to provide more legal secu-Einleitung ! Notfallsituationen, insbesondere außerklinische Reanimationen, sind durch starken Zeitdruck in Kombination mit unzureichenden anamnestischen Informationen über den Patienten gekennzeichnet [1,2]. In dieser Lage müssen Entscheidungen schnell gefasst werden.…”
unclassified